Tuning the 1H NMR paramagnetic relaxation enhancement and local order of [Aliquat]+-based systems mixed with DMSO - Cordeiro, Rui (2021)
Understanding the behavior of a chemical compound at a molecular level is fundamental, not only to explain its macroscopic properties, but also to enable the control and optimization of these properties. The present work aims to characterize a set of systems based on the ionic liquids [Aliquat][Cl] and [Aliquat][FeCl4] and on mixtures of these with different concentrations of DMSO by means of H-1 NMR relaxometry, diffusometry and X-ray diffractometry. Without DMSO, the compounds reveal locally ordered domains, which are large enough to induce order fluctuation as a significant relaxation pathway, and present paramagnetic relaxation enhancement for the [Aliquat][Cl] and [Aliquat][FeCl4] mixture. The addition of DMSO provides a way of tuning both the local order of these systems and the relaxation enhancement produced by the tetrachloroferrate anion. Very small DMSO volume concentrations (at least up to 1%) lead to enhanced paramagnetic relaxation without compromising the locally ordered domains. Larger DMSO concentrations gradually destroy these domains and reduce the effect of paramagnetic relaxation, while solvating the ions present in the mixtures. The paramagnetic relaxation was explained as a correlated combination of inner and outer-sphere mechanisms, in line with the size and structure differences between cation and anion. This study presents a robust method of characterizing paramagnetic ionic systems and obtaining a consistent analysis for a large set of samples having different co-solvent concentrations.